Read and write latency reduction in distributed objects with replication and caching - Toh, Hann Wei. (2008)
We studied the replication and caching strategy employed by several dis-tributed shared memories and implemented it in CORBA, a contemporary dis-tributed object system. The implemented architecture supports the replication of server objects and the caching of the replicas in individual nodes. The thesis defines its consistency properties, which serve as a detailed specification of the system behavior. Among the properties are atomic reads and writes in individual nodes, write order preservation for conflicting writes, program order preservation for non-conflicting writes and asynchronous write propagation.